Caregiver's Knowledge regarding Homecare Management of Spastic Cerebral Palsy Children Under 12 Years Old in Rapareen Province - Farida Salim Faqi-Rahid; Shukir Saleem Hasan (Hawler Medical University, 2022)
Background and objectives: Spasticity, sometimes called hypertonia, makes movement difficult or even impossible. Spastic children with Cerebral Palsy face many health problems that need significant attention at home. This study aimed to assess caregivers' knowledge about home care management of spastic CP children in the Rapareen Region. Methods: A quantitative, descriptive cross-sectional study was carried out in the Rapareen Region of Sulaimani city. The period started from October 1st, 2020, to October 1st, 2021. Purposive (non-probability) sampling techniques of 115 caregivers, who attend rehabilitation centers in Ranya, Chwarqwrne, and Qaladeze in Rapareen province, were respectively recruited to the study. The investigators prepared a questionnaire format after reviewing related literature. Direct interview (face to face) and a home visit was conducted to collect the data. Descriptive statistics SPSS version 25 was used, and statistics of frequencies, percentages, and inferential statistical analysis of Chi-square test and regression were used. Results: The vast majority (98.3%) of the primary caregivers were mothers of spastic CP children. Almost all (94.8) of the caregivers were married. The majority (88.7%) of caregivers were housewives. Less than half (48.7%) of the sample were between 31 to 40 years. More than three quarter (67%) of the sample were male children and more than half (65.2%) were School-age children with Spastic Cerebral Palsy. There was a statistically highly significant association between formal years of education and residency area of caregiver with the caregiver's knowledge at a p-value of 0.020 and 0.003 respectively. Factors significantly associated with caregivers' knowledge of homecare of spastic CP children include the level of education of caregiver, age of caregiver, and height of spastic Cerebral Palsy children. Conclusion: The findings of the present study showed that level of education, age of caregiver, and residency areas are associated with caregiver's knowledge regarding homecare of spastic Cerebral Palsy children.